MATHEMATIC MODEL OF FORECASTING OF EXPANSION OF TEETH CARIES IN HISTORICAL ASPECT - Kaskova, L.F.; Artemyev, A.V. (World of Medicine and Biology, 2012)
Аpplication of a mathematical method of creation of statistical data (a method of the factorial analysis - dot columns), allowed to receive caries model for the XXI century at inhabitants of Poltava, by means of application of materials about ills оf teeth of the population that lived in the territory of Ukraine during copper era–Middle Ages.